On polydispersity and the hard sphere glass transition. Issue 2 (20th November 2014) - Zaccarelli, Emanuela; Liddle, Siobhan M.; Poon, Wilson C. K.
Abstract : The glass transition is smeared out in polydisperse hard spheres due to decoupling between small and large particles. Abstract : We investigate the dynamics of polydisperse hard spheres at high packing fractions ϕ . We use extensive numerical simulations based on an experimentally-realistic particle size distribution (PSD) and compare to commonly-used PSDs such as Gaussian or top hat distribution. We find that the mode of kinetic arrest depends on the PSD's shape and not only on its variance. For the experimentally-realistic PSD we find ageing dynamics even though the density correlators decay fully to zero for ϕ ≥ 0.59. We observe substantial decoupling of the dynamics of the smallest and largest particles. While the smallest particles remain diffusive in all our simulations, a power-law describes the largest-particle diffusion, suggesting an ideal arrest at ϕ c ∼ 0.588. The latter is however averted just before ϕ c, due to the presence of the mobile smallest particles. In addition, we identify that a partial aging mechanism is at work, whose effects are most pronounced for the largest particles. By comparing our results with recent experimental observations of ergodic behavior up to ϕ ∼ 0.6 in a hard-sphere system, we argue that this is an effect of polydispersity, which smears out the glass transition.